Altered metabolic pathways regulate synovial inflammation in rheumatoid arthritis. (11th November 2018) - Fearon, U; Hanlon, M M; Wade, S M; Fletcher, J M
Summary: Rheumatoid arthritis is characterized by synovial proliferation, neovascularization and leucocyte extravasation leading to joint destruction and functional disability. The blood vessels in the inflamed synovium are highly dysregulated, resulting in poor delivery of oxygen; this, along with the increased metabolic demand of infiltrating immune cells and inflamed resident cells, results in the lack of key nutrients at the site of inflammation. In these adverse conditions synovial cells must adapt to generate sufficient energy to support their proliferation and activation status, and thus switch their cell metabolism from a resting regulatory state to a highly metabolically active state. This alters redox-sensitive signalling pathways and also results in the accumulation of metabolic intermediates which, in turn, can act as signalling molecules that further exacerbate the inflammatory response. The RA synovium is a multi-cellular tissue, and while many cell types interact to promote the inflammatory response, their metabolic requirements differ. Thus, understanding the complex interplay between hypoxia-induced signalling pathways, metabolic pathways and the inflammatory response will provide better insight into the underlying mechanisms of disease pathogenesis. Graphical Abstract: